Development of a Dairy-Free Fermented Oat-Based Beverage With Enhanced Probiotic and Bioactive Properties - Chen, Liwei; Wu, Daoyan; Schlundt, Joergen; Conway, Patricia L. (Frontiers in Microbiology, 2020)
Lactobacillus fermentum PC1 with proven probiotic properties was used to ferment oats with added honey to develop a probiotic beverage with enhanced bioactive ingredients. The viable lactobacilli were enumerated during the fermentation and storage at 4 ℃, as well as after exposure to simulated gastrointestinal tract conditions. Good survival was noted both during storage as well as when exposed to the in vitro digestive tract conditions. Comparative analysis of the antioxidant activity, total phenolic content and phenolic composition indicated fermentation improved the total antioxidant capacity and phenolic acid concentration. An increase of more than 50% of gallic acid, catechin, vanillic acid, caffeic acid, p-coumaric acid and ferulic acid was observed in the methanol extracts. Moreover, no significant decrease in the β-glucan content was noted during fermentation and storage. In conclusion, this fermented product has great potential as a functional food with enhanced probiotic survival and increased bioactive ingredients.